2017
DOI: 10.1097/mlr.0000000000000635
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Parity and Addiction Equity Act Evaluation Study

Abstract: Objective The federal Mental Health Parity and Addiction Equity Act (MHPAEA) sought to eliminate historical disparities between insurance coverage for behavioral health (BH) treatment and coverage for medical treatment. Our objective was to evaluate MHPAEA’s impact on BH expenditures and utilization among “carve-in” enrollees. Method We received specialty BH insurance claims and eligibility data from Optum, sampling 5,987,776 adults enrolled in self-insured plans from large employers. An interrupted time ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…An informative difference stands out from comparing the results of these complementary analyses: The level changes in total and plan expenditures are higher in this study (approximately $30 among adults with SUD in both carve-in and carve-out plans versus approximately $1 among all adults in carve-in plans and among all adults in carve-out plans). The expenditure changes observed among the SUD diagnosed sample are all the more notable given that among users of BH specialty services, the subset with SUD diagnoses has much higher pre-parity average per-member per-month total expenditures ($1035) compared to all carve-in users ($331) and all carve-out users ($302) (Ettner et al, 2016; Harwood et al, 2017). At first glance, the greater change in expenditures among the SUD population is not surprising, since 100% of the sample in this paper has a SUD diagnosis, and thus might be expected to increase utilization and expenditures to a greater degree than the other studies' samples which include those with and without SUD diagnoses.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…An informative difference stands out from comparing the results of these complementary analyses: The level changes in total and plan expenditures are higher in this study (approximately $30 among adults with SUD in both carve-in and carve-out plans versus approximately $1 among all adults in carve-in plans and among all adults in carve-out plans). The expenditure changes observed among the SUD diagnosed sample are all the more notable given that among users of BH specialty services, the subset with SUD diagnoses has much higher pre-parity average per-member per-month total expenditures ($1035) compared to all carve-in users ($331) and all carve-out users ($302) (Ettner et al, 2016; Harwood et al, 2017). At first glance, the greater change in expenditures among the SUD population is not surprising, since 100% of the sample in this paper has a SUD diagnosis, and thus might be expected to increase utilization and expenditures to a greater degree than the other studies' samples which include those with and without SUD diagnoses.…”
Section: Discussionmentioning
confidence: 96%
“…Following MHPAEA's historically comprehensive reforms to BH benefits for commercially-sponsored insurance plans, earlier analyses have shown that the resulting increases in specialty BH utilization and expenditures among a population of adult enrollees were modest (Harwood et al, 2017). However, whether these reforms would be associated with utilization and expenditure increases among a population with SUD remained an open question.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be costly for patients over time (French, Popovici, and Tapsell, 2008). Prior work documents that expenditures are substantially higher among privately-insured, non-elderly adults with SUD diagnoses compared to the same population as a whole (Harwood et al 2017; Friedman et al 2017). Since sufficiently generous financial requirements, commonly used insurance benefit design features, can reduce patients’ out-of-pocket expenditures for these services, they are a key determinant of access to SUD treatment.…”
Section: Introductionmentioning
confidence: 99%